Influence of temperature – viscosity effect on ring-journal speed ratio and stability for a hydrodynamic floating ring bearing. Issue 4 (3rd April 2019) - Guo, Hong; Yang, Shuai; Zhang, Shaolin; Zhang, Zebin
Abstract : Purpose: The purpose of this paper is to study the influence of lubricant temperature-viscosity on the performance for a hydrodynamic journal floating ring bearing (FRB), including ring-journal speed ratio and stability. Design/methodology/approach: The finite difference method was used to solve computational models of Reynolds equation, energy equation and temperature–viscosity equation. Dynamic coefficients were obtained based on the floating ring balance. The dynamic model of journal and floating ring was established to deduce the stability criterion of single mass symmetrical rigid FRB rotor system by the Routh–Hurwitz method. The outlet temperature and ring-journal speed ratio under different journal speeds were compared to experimental data. Findings: The temperature–viscosity effect reduces the ring-journal speed ratio and stability of rotor system. According to theoretical and experimental results, the outlet temperature rises and ring-journal ratio drops when the journal speed rises. Originality/value: The temperature–viscosity effect is combined with dynamic characteristics to analyze the stability of the rotor system and lubrication mechanism for an FRB. Influence of temperature–viscosity on the ring-journal ratio and multi-stable regions of system are studied.